Guilt, redemption and reception: representing Roman female suicide - Glendinning, Eleanor Ruth (2011)
This thesis examines representations of Roman female suicide in a variety of genres and periods from the history and poetry of the Augustan age (especially Livy, Ovid, Horace, Propertius and Vergil), through the drama and history of the early Principate (particularly Seneca and Tacitus), to some of the Church fathers (Tertullian, Jerome and Augustine) and martyr acts of Late Antiquity. The thesis explores how the highly ambiguous and provocative act of female suicide was developed, adapted and reformulated in historical, poetic, dramatic and political narratives. The writers of antiquity continually appropriated this controversial motif in order to comment on and evoke debates about issues relating to the moral, social and political concerns of their day: the ethics of a voluntary death, attitudes towards female sexuality, the uses and abuses of power, and traditionally expected female behaviour. In different literary contexts, and in different periods of Roman history, writers and thinkers engaged in this same intellectual exercise by utilising the suicidal female figure in their works.